An investigation into knowledge that HIV positive women have of the prevention of mother to child transmission of HIV - Hude, Ndileka Ivy (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2006.